Disciplinary regimes of ‘care’ and complementary alternative education - Thomson, Pat; Pennacchia, Jodie (Taylor & Francis, 2016)
In schools, the notion of ‘care is often synonymous with welfare and disciplinary regimes. Drawing on Foucault, and a study of alternative education across the UK, and looking in depth at two cases of complementary alternative education, we identify three types of disciplinary regimes at work in schools: (1) dominant performative reward and punishment, (2) team building and (3) therapeutic. We argue that while all three regimes aim to steer identified students back to the norm, the two complementary approaches that we saw avoided the narrow instrumental behaviourist approaches of the dominant pattern. In so doing, they also opened up wider horizons of possibility and ways to be and become.